Vδ2 T-cell engagers bivalent for Vδ2-TCR binding provide anti-tumor immunity and support robust Vγ9Vδ2 T-cell expansion - King, Lisa A.; de Jong, Milon; Veth, Myrthe; Lutje Hulsik, David; Yousefi, Parsa; Iglesias-Guimarais, Victoria; van Helden, Pauline M.; de Gruijl, Tanja D.; van der Vliet, Hans J. (Frontiers in Oncology, 2024)
BackgroundVγ9Vδ2 T-cells are antitumor immune effector cells that can detect metabolic dysregulation in cancer cells through phosphoantigen-induced conformational changes in the butyrophilin (BTN) 2A1/3A1 complex. In order to clinically exploit the anticancer properties of Vγ9Vδ2 T-cells, various approaches have been studied including phosphoantigen stimulation, agonistic BTN3A-specific antibodies, adoptive transfer of expanded Vγ9Vδ2 T-cells, and more recently bispecific antibodies. While Vγ9Vδ2 T-cells constitute a sizeable population, typically making up ~1-10% of the total T cell population, lower numbers have been observed with increasing age and in the context of disease. MethodsWe evaluated whether bivalent single domain antibodies (VHHs) that link Vδ2-TCR specific VHHs with different affinities could support Vγ9Vδ2 T-cell expansion and could be incorporated in a bispecific engager format when additionally linked to a tumor antigen specific VHH. ResultsBivalent VHHs that link a high and low affinity Vδ2-TCR specific VHH can support Vγ9Vδ2 T-cell expansion. The majority of Vγ9Vδ2 T-cells that expanded following exposure to these bivalent VHHs had an effector or central memory phenotype and expressed relatively low levels of PD-1. Bispecific engagers that incorporated the bivalent Vδ2-TCR specific VHH as well as a tumor antigen specific VHH triggered antitumor effector functions and supported expansion of Vγ9Vδ2 T-cells in vitro and in an in vivo model in NOG-hIL-15 mice.ConclusionBy enhancing the number of Vγ9Vδ2 T-cells available to exert antitumor effector functions, these novel Vδ2-bivalent bispecific T cell engagers may promote the overall efficacy of bispecific Vγ9Vδ2 T-cell engagement, particularly in patients with relatively low levels of Vγ9Vδ2 T-cells.